MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP PECAHAN SEDERHANA MELALUI MEDIA KEPINGAN CD (COMPACT DISK) BAGI ANAK KESULITAN BELAJAR - Cica Anwar (Universitas Negeri Padang, 2012)
This Study begius with an assessment of research carried out in SDN 05 kapalo koto padang, there is a 9 year old boy with the initials X who can not recognize the concept of fractional an optimal, where child have disability in naming fractions, indicating fractions, and fractions matching numbers with symbols. This research alms to improve understanding of the concept of simple fractions in the teartcing of mathemations through the medium of CD (Compact Disk). Date analysis results in a condition and results of date between the condition seen that before treatment is given usin the medium CD (Compact Disk) on baseline conditions, children’s ability to say fractions. Children’s ability to demonstrate fractions. children ability to match the fraction with the symbol number. This proves medium CD (Compact Disk) can improve the ability of understanding the concept of fraction for the child’s learning disability. For medium teachers should use there CD (Compact Disk) in the process of teaching and learning (PBM) for child learning disability at SDN 05 Kapalo Koto Padang.